The Age-adjusted Charlson Comorbidity Index predicts post-operative delirium in the elderly following thoracic and abdominal surgery: A prospective observational cohort study - Liu, Jing; Li, Jianli; He, Jinhua; Zhang, Huanhuan; Liu, Meinv; Rong, Junfang (Frontiers in Aging Neuroscience, 2022)
Background: Postoperative delirium (POD) presents as a serious neuropsychiatric syndrome in the elderly undergoing thoracic and abdominal surgery, which is mostly associated with poor prognosis. The Age-adjusted Charlson Comorbidity Index (ACCI) has been widely recognized as an independently predictive factor for overall survival rate and mortality in various surgeries. However, no studies demonstrated the potential relationship between ACCI and POD. The current study was to explore the correlation between ACCI and POD, and determine the predictive effect of ACCI on POD in the elderly after thoracic and abdominal surgery. Methods: Total 184 patients (≥60 years) who underwent thoracic and abdominal surgery from 2021.10 to 2022.5 were enrolled in this prospective observational cohort study. ACCI was calculated by weighting comorbidities and age. POD was diagnosed using Confusion Assessment Method (CAM) twice a day in the first three days after surgery. The Visual Analog Scale (VAS) was applied to measure postoperative pain at rest and in motion. All demographic and perioperative data were compared in patients with POD and without POD. ACCI and other variables were analyzed by univariate and multivariate logistic regression analysis. The characteristic curve of ROC was used to further evaluate the accuracy of ACCI to predict POD. Results: POD was diagnosed in 36 of 184 patients included in our study. The prevalence of POD in the elderly after thoracic and abdominal surgery was 19.6%. The outcomes by multivariate regression analysis showed the independent risk factors for POD were ACCI (OR:1.834; 95%CI:1.434-2.344; P＜0.001), preoperative MMSE scores (OR:0.873; 95%CI:0.767-0.994; P=0.040), serum albumin(OR:0.909; 95%CI:0.826-1.000; P=0.049) and pain scores in the postoperative third day (OR:2.013; 95%CI:1.459-2.778; P＜0.001). ACCI can predict POD more accurately with the largest area under curve (AUC) of 0.794 and sensitivity of 0.861 respectively. Conclusion: ACCI, preoperative MMSE scores, serum albumin and postoperative pain were independently associated with POD in geriatric patients following thoracic and abdominal surgery. Moreover, ACCI may become an accurate indicator to predict POD early.